Enhanced anti-inflammatory and ulcerogenicity of Ibuprofen microsphere formulations using Irvingia wombolu fat (IRW) and moringa oil (MO) as co-lipids - Thaddeus H. Gugu; Geraldine C. Agu; Emmanuel M. Uronnachi; Salome A. Chime (BMC, 2023)
Abstract Ibuprofen is a member of the propionic acid class of nonsteroidal anti-inflammatory drugs (NSAIDs) with anti-inflammatory, analgesic, and antipyretic activities used to relieve a variety of pains. The objective of this study was to formulate, characterize and evaluate the in vitro and in vivo properties of ibuprofen formulated as solid lipid microspheres (SLMs) for enhanced delivery. The mixtures of Irvingia wombolu fat (IRW) and moringa oil (MO) each with Phospholipon® 90G (PL90G) at the ratio of 2:1 w/w were prepared by fusion, characterized and used to prepare SLMs. The SLMS were thereafter evaluated using the following parameters: particle size and morphology, stability, and encapsulation efficiency EE (%). In vitro release was carried out in phosphate buffer (pH 7.4). The ibuprofen based SLMs were also evaluated for anti-inflammatory and anti-ulcer effects using animal models. The pH showed significant increase after two months of formulation with a maximum value of 6.4 while the EE obtained were 95.6, 89.4 and 61.6% for SLMs formulated with lipid matrix of Phospholipon® 90G (1% and 2%), and MO (1%) respectively. The in vitro release showed maximum release of 87.8 and 98.97% of the two different lipid-based formulations while anti-inflammatory effect was up to 89.90% after 5 h of inducing inflammation. The SLMs did not show any lesion thus conferring gastroprotection on the formulations. The SLMs exhibited good anti-inflammatory property with gastroprotective action.